Purifying the nation: population exchange and ethnic cleansing in Nazi-allied Romania - Solonarʹ, Vladimir Anatolevič (Johns Hopkins Univ. Press [u.a.], 2010)
The national ideal -- One ideal or many? : a short history -- Colonization and resettlement : early Romanian experience -- Into the Nazis' fold -- Romanian eugenics : racism without a "race" -- Modern science and nationalism : two Romanian cases -- The population exchange with Bulgaria : "an opportunity missed"? -- Model province -- The new regime -- The project : "Model province" -- Cleansing the terrain, I : mass murder -- Cleansing the terrain, II : deportation -- The cost of Utopia -- What did they know? What did they do? -- Between the dream and reality -- Romanianization -- Deporting Roma -- Stopping deportations and changing course -- "Voluntary" population exchange with Bulgaria -- Getting ready for the world that never came : planning population exchanges -- Letting them out, and keeping them out